2014
DOI: 10.1007/s40685-014-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

Ethical requirement and financial interest: a literature review on socially responsible investing

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 142 publications
(170 reference statements)
5
71
0
6
Order By: Relevance
“…However, emotional inclination, ingrained thought patterns, and the psychological biases of different human beings-that is, the behavioral paradigm of financial decision-making-describes how investors perceive the world and make investment decision [39][40][41]. Investment decision was previously followed by an ordinary triangle covering risk, liquidity, and return, however, a growing number of investors nowadays use the phenomenal square, covering liquidity, risk, return and sustainability [42]. Henceforth, the investment decision process of investors is not unique to all investors, but rather is heterogeneous to various investors.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…However, emotional inclination, ingrained thought patterns, and the psychological biases of different human beings-that is, the behavioral paradigm of financial decision-making-describes how investors perceive the world and make investment decision [39][40][41]. Investment decision was previously followed by an ordinary triangle covering risk, liquidity, and return, however, a growing number of investors nowadays use the phenomenal square, covering liquidity, risk, return and sustainability [42]. Henceforth, the investment decision process of investors is not unique to all investors, but rather is heterogeneous to various investors.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…While ethical investing has ancient origins in Jewish, Christian, and Islamic traditions, the roots of the modern SRI development can be found in the political climate of the 1960s (Renneboog et al 2008). A comprehensive overview of the existing literature on SRI is provided by von Wallis and Klein (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Orlitzky et al [34] found a moderate positive correlation between CSR and financial performance. Among the most recent panoramic papers, Von Wallis and Klein [35] showed that the dominant conclusion of the empirical studies is that a significant difference between the performances of SRI and conventional funds cannot be proved, although other studies identify underperformance or outperformance. Their respective numbers were: 15 for indifference (p. 84), 6 for underperformance (p. 79), and 14 for outperformance (p. 81).…”
Section: Corporate Social Responsibility and Socially Responsible Invmentioning
confidence: 99%
“…Most of these studies (p. 84) apply risk-adjusted performance measures, which shows that the impact on accounting results has received less attention. Von Wallis and Klein [35] (p. 83) signaled that a cause of positive results could be that "managers will only take those SR decisions that improve corporate value". Junkus and Berry [36] provided a deep analysis of the critical issues on SRI.…”
Section: Corporate Social Responsibility and Socially Responsible Invmentioning
confidence: 99%